2017
DOI: 10.1590/1982-0224-20160132
|View full text |Cite
|
Sign up to set email alerts
|

A new genus of Neotropical rheophilic catfishes, with four new species (Teleostei: Siluriformes: Pseudopimelodidae)

Abstract: Rhyacoglanis, a new genus of the South American freshwater catfish family Pseudopimelodidae is described from cis-Andean portions of the continent. Rhyacoglanis is distinguished from other genera of the family by three synapomorphies: presence of a light blotch on the cheek; a connection between the middle of the dark caudal-fin stripe and the dark caudal-peduncle pigmentation; and 30-35 total vertebrae. Species of Rhyacoglanis are rheophilic and strongly associated with rapids and other swift-flowing waters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(66 citation statements)
references
References 21 publications
9
52
1
4
Order By: Relevance
“…However, the findings of heart-haped gas bladder in the two new species described herein, P. mangurus, and P. schultzi, do not provide support to the dumbbell-shaped gas bladder (Birindelli & Shibatta, 2011) as synapomorphy of the clade [Cruciglanis, Pseudopimelodus] Rhyacoglanis] (Shibatta & Vari, 2017). Compared with Shibatta & Vari (2017), this study also found a wider range of number of vertebrae (38-44 vs. 41-42), partial fusion between predorsal and subdorsal bands (vs. absent), and short maxillary barbels, falling short of vertical through dorsal-fin origin, although they are shorter in P. magnus and do not reach the opercular margin in P. atricaudus.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…However, the findings of heart-haped gas bladder in the two new species described herein, P. mangurus, and P. schultzi, do not provide support to the dumbbell-shaped gas bladder (Birindelli & Shibatta, 2011) as synapomorphy of the clade [Cruciglanis, Pseudopimelodus] Rhyacoglanis] (Shibatta & Vari, 2017). Compared with Shibatta & Vari (2017), this study also found a wider range of number of vertebrae (38-44 vs. 41-42), partial fusion between predorsal and subdorsal bands (vs. absent), and short maxillary barbels, falling short of vertical through dorsal-fin origin, although they are shorter in P. magnus and do not reach the opercular margin in P. atricaudus.…”
Section: Discussioncontrasting
confidence: 61%
“…It differs from P. bufonius, P. charus, and P. mangurus by having a heart-shaped gas bladder (vs. dumbbell-shaped bladder; Fig. 6; (Shibatta & Vari, 2017). It differs from P. atricaudus by having the anterior margin of the dorsal-fin spine serrated (vs. smooth).…”
Section: Molecular Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…(this paper), Hypophthalmus edentatus = Hypophthalmus oremaculatus (see Littmann et al 2015), "Pseudopimelodus" pulcher = Rhyacoglanis sp. (see Shibatta & Vari 2017).…”
Section: Fish Identificationmentioning
confidence: 99%